The measurement on the effectiveness of management system in wealth supremacy agency / Abd Quddus Mat Said - Mat Said, Abd Quddus (Faculty of Business and Management, 2009)
Management is very important as it will serve as a basis for companies’ action measures this is because management system will guide the company in any decision making such as planning, leading, organizing and also controlling. Therefore, for the company to maintain and move to higher level affective management system will be act as backbone for the company’s strategies and later turn to action that will determine the overall result of success. In financial industries, the company faces many challenges especially to the company that involved directly in unit trust industries. This is due to the unpredictable market condition and public awareness. CIMB Wealth Advisors is among the company that involved directly in unit trust industries. Therefore, it is very important for the company to effectively adapting effective management system so that the company will be able to stand strong in this industry. Under the concept of managing your own business, CIMB Wealth Advisors have encouraged and provide certain guidelines so that the entire consultant will be able to own their agency. As it will improve leadership skills, it will also help CIMB Wealth Advisors to monitor consultants’ performance in smaller scope. Wealth Supremacy Agency is one of the agencies that are established under the concept of managing your own business. As the agency involve in providing total financial solution to the clients, they are facing challenges from this industry. This study will focus on the management challenges and also its counter actions to face the challenges. Besides that, this study also will explain on fund performances of unit trust fund managed under CIMB Principal Asset Management.